Effects of a Psychomotor Intervention on Water in the Quality of Life of Adults with Intellectual and Developmental Disabilities - Nádia Jardim; Sofia Santos (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2016)
Improving the quality of life (QOL) of persons with intellectual and developmental disabilities (IDD) is one of the goals of supports providers. This study's goal is to analyze the contribution of a psychomotor intervention in water on the QOL and aquatic skills of adults with IDD. All 29 participants, four males and twenty-five females, with ages ranging from 19 to 45 years old (28.55±5.49), diagnosed with "mild" and "moderate" IDD at the Occupational Activity Center (OAC), were evaluated by the Portuguese version of Personal Outcomes Scale and the Ficha de Avaliação do Comportamento em Meio Aquático in three different moments (baseline, final and retention) A Psychomotor Program Intervention in water was implemented during four months, of three 50 minute sessions per week. Findings showed benefits of psychomotor intervention in the promotion of some QOL domains and aquatic skills of adults with IDD. Differences were found on QOL domains and aquatic skills. Implications for future research and psychomotor practice are discussed.